High-strength and high-stability polyester cord thread and preparation method thereof
By adding 3-aminopropyltriethoxysilane and caffeic acid to the spinning oil agent of the polyester cord, thiol compounds were prepared in combination with the amidation reaction to form a crosslinking network structure, the problems of poor interfacial adhesion and poor thermal properties of the polyester cords were solved, and the adhesion strength and material stability of the fiber and rubber were significantly improved.
Patent Information
- Application Number
- CN202510130644.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-06
AI Technical Summary
During the use of the existing polyester cords, due to poor interface adhesion and poor thermal performance, the adhesion between tire components is reduced.
By adding 3-aminopropyltriethoxysilane to the spinning oil agent and performing amidation reaction using the amino group and caffeic acid in the activator, catechol groups with adhesion properties are introduced to enhance the adhesion of the polyester fiber. At the same time, glutathione is grafted onto the polylysine backbone through amidation reaction to prepare a thiol compound, and a thiol-ene click-through reaction occurs with the double bond on the surface of the modified fiber to form a strong crosslinking network structure.
It significantly improves the bonding strength between fiber and rubber, reduces interface debonding, and improves the stability and mechanical strength of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester cords, in particular to a high-strength and high-stability polyester cord and a preparation method thereof. Background Art
[0002] Tires are typical rubber products, which are composite materials reinforced by rubber and cords. At present, the tire industry has formed a situation where a variety of skeleton materials with different characteristics coexist, such as steel wire, rayon, nylon, polyester, and aramid. Among them, polyester cord has become the most widely used fiber skeleton material in tires due to its high strength, good dimensional stability and high cost performance.
[0003] As a skeleton material, polyester fiber can significantly improve the strength and dimensional stability of rubber products. However, since polyester fiber only contains ester bonds, and has an alcohol hydroxyl group and a carboxyl group at each end, it has fewer surface active groups and lacks hydrogen bonds that form a bond with rubber, resulting in poor interfacial adhesion between polyester fiber and rubber matrix. In addition, amine accelerators in tire rubber may migrate to the surface of polyester fiber during use, resulting in aminolysis of ester bonds. Polyester cord generates a lot of heat during tire use, thereby reducing the adhesion between tire components.
[0004] Therefore, we propose a high-strength and high-stability polyester cord and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a high-strength and high-stability polyester cord and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high-strength and high-stability polyester cord comprises the following steps:
[0008] Step S1: subjecting high-viscosity polyester chips to screw melt spinning, air blowing cooling and forming, initial application of spinning oil, heat drawing, heat setting, relaxation heat treatment, impregnation with an activator, and winding to obtain preactivated polyester fibers, and subjecting the preactivated polyester fibers to heat treatment and storage to obtain modified polyester fibers;
[0009] The spinning oil is a mixed solution containing 3-aminopropyltriethoxysilane, the concentration of the oil is 15-20wt%, and the 3-aminopropyltriethoxysilane accounts for 5-20wt% in the spinning oil;
[0010] The process conditions of the heat drawing are: the temperature of the hot roller is 90-150°C, and the speed of the hot drawing roller is 3000m / min-4000m / min; the process conditions of the heat setting and relaxation heat treatment are: the temperature of the hot roller is 200-255°C, and the speed of the hot roller is 4500m / min-6000m / min;
[0011] The activator is a mixed solution containing caffeic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and water;
[0012] The heat treatment storage specifically comprises: heat treating the preactivated polyester fiber at a temperature of 50-100° C. for a treatment time of 96-110 hours;
[0013] Step S2: the modified polyester fiber is paralleled, twisted, and heat-set to obtain a polyester strand; the polyester strand is twisted into shape by a twisting machine to obtain a twisted cord;
[0014] Step S3: immersing the twisted cord into a first adhesive solution for a primary immersion treatment, irradiating it with ultraviolet light, and then immersing it into a second adhesive solution for a secondary immersion treatment, and obtaining a polyester cord after drying and heat treatment.
[0015] Furthermore, in step S1, the mixed solution of 3-aminopropyltriethoxysilane is composed of deionized water and 3-aminopropyltriethoxysilane in a mass ratio of (2-3): (0.2-0.4).
[0016] Furthermore, in step S1, the mass ratio of caffeic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and water is 1:(0.1-0.2):(15-20).
[0017] Furthermore, in step S2, the heat setting process conditions are: heat setting for 30-80 minutes at a temperature of 60-80° C. and a pressure of 0.05-0.08 MPa.
[0018] Furthermore, in step S2, the number of polyester strands is 2.
[0019] Furthermore, in step S3, the preparation method of the first adhesive solution is as follows:
[0020] The mercapto compound, 2-mercaptobenzothiazole, ammonia water and deionized water are mixed evenly, and then a photoinitiator and styrene-butadiene latex are added and mixed evenly to obtain a first adhesive solution.
[0021] Furthermore, the first adhesive solution includes the following components by weight: 5-10 parts of mercapto compounds, 1-3 parts of photoinitiators, 3-5 parts of 2-mercaptobenzothiazole, 2-4 parts of styrene-butadiene latex, 10-40 parts of ammonia water, and 30-50 parts of deionized water.
[0022] Furthermore, the preparation method of the thiol compound is as follows:
[0023] Glutathione, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide, N,N-diisopropylethylamine and 4-pyrrolidinylpyridine are mixed evenly, deionized water and anhydrous ethanol are added, and the mixture is stirred at 20-30° C. for 30-50 minutes. Polylysine is added, and the mixture is stirred for 20-24 hours. The mixture is filtered, rotary evaporated and dried to obtain a thiol compound.
[0024] In the above technical scheme, glutathione is grafted onto the main chain of polylysine (LYS) containing a large number of amino and carboxyl groups through an amidation reaction to obtain a thiol compound, which has excellent bonding properties and can further undergo a thiol-ene click reaction with the double bond in caffeic acid.
[0025] Furthermore, the mass ratio of glutathione, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide, N,N-diisopropylethylamine and 4-pyrrolidinopyridine is 1:(1.8-2.0):(1.0-1.2):(3.5-3.8):(0.02-0.04).
[0026] Furthermore, the volume ratio of deionized water to anhydrous ethanol is 1:2, the ratio of glutathione to deionized water is 5 g / 100 mL, and the mass of polylysine is 1.5-2.0 times the mass of glutathione.
[0027] Furthermore, in step S3, the preparation method of the second adhesive solution is as follows: trimethylolpropane triglycidyl ether and deionized water are mixed evenly, triethylenetetramine is added, and the mixture is stirred at 60-80°C for 30-50 minutes, and then the styrene-butadiene latex solution is added, and the mixture is stirred at 20-30°C for 1-2 hours to obtain the second adhesive solution.
[0028] Furthermore, the second adhesive solution comprises the following components by weight: 5-10 parts of trimethylolpropane triglycidyl ether, 1-5 parts of triethylenetetramine, 100-110 parts of styrene-butadiene latex solution, and 90-180 parts of deionized water.
[0029] In the above technical scheme, the amino groups, epoxy groups and other groups in the second adhesive solution react with the polar groups such as amide groups, amino groups, hydroxyl groups on the twisted cord treated with the first adhesive solution. In addition, the styrene-butadiene latex dispersed in the resin network can participate in the rubber vulcanization to form cross-links, thereby obtaining excellent interface adhesion between the fiber and the rubber.
[0030] Furthermore, the concentration of the styrene-butadiene latex solution is 40wt%.
[0031] Furthermore, in step S3, the time for the first immersion treatment is 10-30 minutes; and the time for the second immersion treatment is 1-3 minutes.
[0032] Furthermore, in step S3, the ultraviolet irradiation process conditions are: irradiation with 360-400nm ultraviolet rays for 5-20min, and an irradiation intensity of 20-35mW / cm 2 .
[0033] Furthermore, in step S3, the process conditions of drying and heat treatment are: drying at 120-180° C. for 20-40 min, and then heat treatment at 200-240° C. for 0.5-3.0 min.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. A high-strength and high-stability polyester cord and a preparation method thereof of the present invention comprises the following steps: adding 3-aminopropyltriethoxysilane to a spinning oil to introduce an amino group, and then utilizing the amino group and caffeic acid in an activator to undergo an amidation reaction to introduce a catechol group having adhesion properties, thereby improving the adhesion of the polyester fiber, and simultaneously introducing a double bond to provide a subsequent reaction site to obtain a preactivated polyester fiber; heat-treating the preactivated polyester fiber for storage to improve its stability to obtain a modified polyester fiber; and on this basis, performing a resin dipping treatment on a twisted cord made of the modified polyester fiber to greatly improve the adhesion between the polyester fiber and the rubber material.
[0036] 2. A high-strength and high-stability polyester cord and a preparation method thereof of the present invention, wherein glutathione is grafted onto the main chain of polylysine (LYS) through an amidation reaction to obtain a biomass-based adhesive, namely a thiol compound, which has excellent bonding properties; the thiol compound is used as an adhesive, 2-mercaptobenzothiazole is used as a constant adhesive, and styrene-butadiene rubber is used as an elastomer. Under the action of a photoinitiator, a thiol-ene click reaction can be further carried out with the double bonds on the surface of the modified fiber to form a strong cross-linked network structure, which can significantly improve the bonding strength between the fiber and the rubber and reduce the interface debonding phenomenon;
[0037] Then, a second adhesive solution is used for dipping treatment, and the amino group, epoxy group and other groups in the second adhesive solution react with the polar groups such as amide group, amino group, hydroxyl group and so on on the twisted cord treated with the first adhesive solution, thereby forming a tighter cross-linked network. In addition, the styrene-butadiene latex solution dispersed in the resin network can participate in the vulcanization of the rubber to form cross-links, further enhancing the interfacial adhesion between the fiber and the rubber. Through two dipping treatments, the interfacial bonding between the fiber and the rubber is significantly improved, reducing the risk of interfacial peeling and ensuring the stability of the material. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In this embodiment, the high-viscosity polyester chips are of the brand Changzhou Huarun CR-882; the styrene-butadiene latex is of the model YT-14, which is sourced from Jiangsu Yatai Chemical Co., Ltd.; and the oil is of the model Fasavin 2744.
[0040] In the following examples and comparative examples, 1 part is equal to 10 g.
[0041] Embodiment 1: A method for preparing a high-strength and high-stability polyester cord, comprising the following process:
[0042] Step S1: subjecting high-viscosity polyester chips to screw melt spinning, air blowing cooling and forming, initial application of spinning oil, heat drawing, heat setting, relaxation heat treatment, impregnation with an activator, and winding to obtain preactivated polyester fibers, and subjecting the preactivated polyester industrial yarns to heat treatment and storage to obtain modified polyester fibers;
[0043] The spinning oil is a mixed solution containing 3-aminopropyltriethoxysilane, the concentration of the oil is 15wt%, and 3-aminopropyltriethoxysilane accounts for 5wt% of the spinning oil; the mixed solution of 3-aminopropyltriethoxysilane is composed of deionized water and 3-aminopropyltriethoxysilane in a mass ratio of 2:0.2;
[0044] The process conditions of the heat drawing are: the temperature of the hot roller is 90°C, and the speed of the hot drawing roller is 3000m / min; the process conditions of the heat setting and relaxation heat treatment are: the temperature of the hot roller is 200°C, and the speed of the hot roller is 4500m / min;
[0045] The activator is a mixed solution containing caffeic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and water in a mass ratio of 1:0.1:15;
[0046] The heat treatment storage is specifically as follows: the pre-activated polyester fiber is heat treated at a temperature of 50° C. for a treatment time of 96 hours;
[0047] Step S2: After the modified polyester fiber is paralleled, twisted, and heat-set (heat-set for 30 minutes at a temperature of 60° C. and a pressure of 0.05 MPa), a polyester strand is obtained; two strands of polyester strands are twisted into shape by a twisting machine to obtain a twisted cord;
[0048] Step S3: The twisted cord is immersed in the first adhesive solution for 10 minutes, and irradiated with 360nm ultraviolet light for 5 minutes with an irradiation intensity of 20mW / cm 2 , then immersed in the second adhesive solution for 1 minute, dried at 120° C. for 20 minutes, and then heat treated at 200° C. for 0.5 minutes to obtain a polyester cord;
[0049] In step S3, the preparation method of the first adhesive solution is as follows:
[0050] 5 parts of mercapto compound, 3 parts of 2-mercaptobenzothiazole, 10 parts of ammonia water and 30 parts of deionized water are mixed evenly, and then 1 part of photoinitiator and 2 parts of styrene-butadiene latex are added and mixed evenly to obtain a first adhesive solution;
[0051] The preparation method of the thiol compound is as follows:
[0052] 5 parts of glutathione, 9 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 5 parts of N-hydroxysuccinimide, 17.5 parts of N,N-diisopropylethylamine and 0.1 parts of 4-pyrrolidinylpyridine were mixed evenly, 100 mL of deionized water and 200 mL of anhydrous ethanol were added, and the mixture was stirred at 20°C for 30 min, 7.5 parts of polylysine were added, and the mixture was stirred for 20 h. After filtering, rotary evaporation and drying, a thiol compound was obtained;
[0053] In step S3, the preparation method of the second adhesive solution is as follows: 5 parts of trimethylolpropane triglycidyl ether and 90 parts of deionized water are mixed evenly, 1 part of triethylenetetramine is added, and the mixture is stirred at 60°C for 30 minutes, and then 100 parts of styrene-butadiene latex solution are added, and the mixture is stirred at 20°C for 1 hour to obtain a second adhesive solution.
[0054] Embodiment 2: A method for preparing a high-strength and high-stability polyester cord, comprising the following process:
[0055] Step S1: subjecting high-viscosity polyester chips to screw melt spinning, air blowing cooling and forming, applying spinning oil, heat drawing, heat setting, relaxation heat treatment, impregnation with an activator, and winding to obtain preactivated polyester fibers, and subjecting the preactivated polyester industrial yarns to heat treatment and storage to obtain modified polyester fibers;
[0056] The spinning oil is a mixed solution containing 3-aminopropyltriethoxysilane, the concentration of the oil is 18wt%, and 3-aminopropyltriethoxysilane accounts for 15wt% of the spinning oil; the mixed solution of 3-aminopropyltriethoxysilane is composed of deionized water and 3-aminopropyltriethoxysilane in a mass ratio of 2.5:0.3;
[0057] The process conditions of the heat drawing are: the temperature of the hot roller is 100°C, and the speed of the hot drawing roller is 3500m / min; the process conditions of the heat setting and relaxation heat treatment are: the temperature of the hot roller is 220°C, and the speed of the hot roller is 5000m / min;
[0058] The activator is a mixed solution containing caffeic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and water in a mass ratio of 1:0.15:18;
[0059] The heat treatment storage specifically comprises: heat treating the preactivated polyester fiber at a temperature of 50-100° C. for a treatment time of 96-110 hours;
[0060] Step S2: After the modified polyester fiber is paralleled, twisted, and heat-set (heat-set for 50 minutes at a temperature of 70° C. and a pressure of 0.06 MPa), a polyester strand is obtained; two strands of polyester strands are twisted into shape by a twisting machine to obtain a twisted cord;
[0061] Step S3: The twisted cord is immersed in the first adhesive solution for 20 minutes, and irradiated with 380nm ultraviolet light for 10 minutes with an irradiation intensity of 25mW / cm 2 , then immersed in the second adhesive solution for 2 minutes, dried at 140° C. for 30 minutes, and then heat treated at 220° C. for 1 minute to obtain a polyester cord;
[0062] In step S3, the preparation method of the first adhesive solution is as follows:
[0063] 7 parts of mercapto compound, 4 parts of 2-mercaptobenzothiazole, 30 parts of ammonia water and 40 parts of deionized water are mixed evenly, and then 2 parts of photoinitiator and 3 parts of styrene butadiene latex are added and mixed evenly to obtain a first adhesive solution;
[0064] The preparation method of the thiol compound is as follows:
[0065] 7 parts of glutathione, 13 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 8 parts of N-hydroxysuccinimide, 25 parts of N,N-diisopropylethylamine and 0.21 parts of 4-pyrrolidinylpyridine were mixed evenly, 140 mL of deionized water and 280 mL of anhydrous ethanol were added, and the mixture was stirred at 25°C for 40 min, 12 parts of polylysine were added, and the mixture was stirred for 22 h. After filtering, rotary evaporation and drying, a thiol compound was obtained;
[0066] In step S3, the preparation method of the second adhesive solution is as follows: 8 parts of trimethylolpropane triglycidyl ether and 130 parts of deionized water are mixed evenly, 3 parts of triethylenetetramine are added, and the mixture is stirred at 70°C for 40 minutes, and then 105 parts of styrene-butadiene latex solution are added, and the mixture is stirred at 25°C for 1.5 hours to obtain a second adhesive solution.
[0067] Embodiment 3: A method for preparing a high-strength and high-stability polyester cord, comprising the following process:
[0068] Step S1: subjecting high-viscosity polyester chips to screw melt spinning, air blowing cooling and forming, initial application of spinning oil, heat drawing, heat setting, relaxation heat treatment, impregnation with an activator, and winding to obtain preactivated polyester fibers, and subjecting the preactivated polyester industrial yarns to heat treatment and storage to obtain modified polyester fibers;
[0069] The spinning oil is a mixed solution containing 3-aminopropyltriethoxysilane, the concentration of the oil is 20wt%, and 3-aminopropyltriethoxysilane accounts for 20wt% of the spinning oil; the mixed solution of 3-aminopropyltriethoxysilane is composed of deionized water and 3-aminopropyltriethoxysilane in a mass ratio of 3:0.4;
[0070] The process conditions of the heat drawing are: the temperature of the hot roller is 150°C, and the speed of the hot drawing roller is 4000m / min; the process conditions of the heat setting and relaxation heat treatment are: the temperature of the hot roller is 255°C, and the speed of the hot roller is 6000m / min;
[0071] The activator is a mixed solution containing caffeic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and water in a mass ratio of 1:0.2:20;
[0072] The heat treatment storage is specifically as follows: heat treating the preactivated polyester fiber at a heat treatment temperature of 100° C. for a treatment time of 110 hours;
[0073] Step S2: After the modified polyester fiber is paralleled, twisted, and heat-set (heat-set for 80 minutes at a temperature of 80° C. and a pressure of 0.08 MPa), a polyester strand is obtained; two strands of polyester strands are twisted into shape by a twisting machine to obtain a twisted cord;
[0074] Step S3: The twisted cord is immersed in the first adhesive solution for 30 minutes, and irradiated with 400nm ultraviolet light for 20 minutes with an irradiation intensity of 35mW / cm 2 , then immersed in the second adhesive solution for 3 minutes, dried at 180° C. for 40 minutes, and then heat treated at 240° C. for 3.0 minutes to obtain a polyester cord;
[0075] In step S3, the preparation method of the first adhesive solution is as follows:
[0076] 10 parts of mercapto compound, 5 parts of 2-mercaptobenzothiazole, 40 parts of ammonia water and 50 parts of deionized water are mixed evenly, and then 3 parts of photoinitiator and 4 parts of styrene butadiene latex are added and mixed evenly to obtain a first adhesive solution;
[0077] The preparation method of the thiol compound is as follows:
[0078] 10 parts of glutathione, 20 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, 12 parts of N-hydroxysuccinimide, 38 parts of N,N-diisopropylethylamine and 4 parts of 4-pyrrolidinylpyridine were mixed evenly, 200 mL of deionized water and 400 mL of anhydrous ethanol were added, and the mixture was stirred at 30°C for 50 min, 20 parts of polylysine were added, and the mixture was stirred for 24 h. After filtering, rotary evaporation and drying, a thiol compound was obtained;
[0079] In step S3, the preparation method of the second adhesive solution is as follows: 10 parts of trimethylolpropane triglycidyl ether and 180 parts of deionized water are mixed evenly, 5 parts of triethylenetetramine are added, and the mixture is stirred at 80°C for 50 minutes, and then 110 parts of styrene-butadiene latex solution are added, and the mixture is stirred at 30°C for 2 hours to obtain a second adhesive solution.
[0080] Comparative Example 1: A method for preparing a high-strength and high-stability polyester cord, comprising the following processes:
[0081] Compared with Example 2, Comparative Example 1 does not include step S1, and the modified polyester fiber is replaced with commercially available polyester fiber (1100 dtex, HMLS industrial yarn, sourced from Jiangsu Taiji Industrial New Materials Co., Ltd.), and the other steps are the same as those in Example 2.
[0082] Comparative Example 2: A method for preparing a high-strength and high-stability polyester cord, comprising the following processes:
[0083] Compared with Example 2, Comparative Example 2 does not include step S3, the twisted cord prepared in step S2 is the polyester cord, and the other steps are the same as those in Example 2.
[0084] Comparative Example 3: A method for preparing a high-strength and high-stability polyester cord, comprising the following processes:
[0085] Step S3: The twisted cord is immersed in the first adhesive solution for 20 minutes, and irradiated with 380nm ultraviolet light for 10 minutes with an irradiation intensity of 25mW / cm 2 , a polyester cord is obtained; compared with Example 2, Comparative Example 3 does not use the second adhesive solution for impregnation treatment, and the other steps are the same as Example 2.
[0086] Comparative Example 4: A method for preparing a high-strength and high-stability polyester cord, comprising the following process:
[0087] Step S3: immersing the twisted cord in the second adhesive solution for 2 minutes, drying at 140°C for 30 minutes, and then heat treating at 220°C for 1 minute to obtain the polyester cord; compared with Example 2, Example 4 does not use the first adhesive solution for immersion treatment, and the other steps are the same as Example 2.
[0088] Experiment: The polyester cords obtained in Examples 1-3 and Comparative Examples 1-4 were used to prepare samples, and their properties were tested and the test results were recorded:
[0089] The H adhesion was determined with reference to GB / T 2942-2009 "Determination of static adhesion strength between vulcanized rubber and fiber cord - H extraction method". The experimental steps were as follows: the rubber mix was made using the formula specified in GB / T 32105-2015, and the rubber mix was cut into strips of 200mm×10mm×10mm. The cut strips were embedded into the grooves of the upper and lower templates, and then the polyester cord was fixed in the groove of the mold. After the mold was closed, the vulcanization treatment was carried out. The temperature of the flat vulcanizer was set to 160°C, the pressure to 15Mpa, and the time to 90min. After the vulcanization, the samples were cut and parked for 16h before testing. The tensile speed was 100m / min, and at least 8 samples were tested. The maximum extraction force was recorded and the average value was taken.
[0090] The fatigue resistance test was carried out according to the GB / T 30315-2013 standard. The polyester cord was subjected to a bending fatigue test under the following conditions: movement frequency 2.5 Hz, load 9.8 N, fatigue times 1×10 5 , determine the breaking strength retention rate after fatigue test, refer to GB / T 32108-2015 test standard to determine the breaking strength, use an electronic tensile testing machine, select a special cord breaking fixture, set the upper and lower fixtures to 250mm, and set the tensile testing machine rate to 300mm / min.
[0091] The test results are as follows:
[0092] H H Adhesion strength / N Breaking strength retention rate / % Example 1 150.7 84.6 Example 2 154.8 85.7 Example 3 153.6 85.2 Comparative Example 1 132.4 74.3 Comparative Example 2 121.2 70.4 Comparative Example 3 142.8 80.6 Comparative Example 4 146.5 82.5
[0093] According to the data in the above table, we can clearly draw the following conclusions:
[0094] 1. Compared with Examples 1-3, the H adhesion and breaking strength retention of the product obtained in Comparative Example 1 are both reduced, indicating that compared with commercially available polyester fibers, the modified polyester fiber prepared by the present invention has better interface bonding strength, thereby effectively improving the bonding performance and overall mechanical strength of the material.
[0095] 2. Compared with Examples 1-3, the H adhesion and breaking strength retention of the products obtained in Comparative Examples 2 and 3 are both reduced, which indicates that the present invention can enhance the interfacial bonding force between the fiber and the rubber through two dipping treatments; at the same time, not using the second adhesive solution for dipping treatment will lead to a weakened bonding force between the adhesive and the fiber, thereby affecting the durability of the material.
[0096] 3. Compared with Examples 1-3, the H adhesion and breaking strength retention of the product obtained in Example 4 are both reduced. It can be seen that when the first adhesive solution is not used for impregnation treatment, the bonding force between the fiber and the rubber will be weakened, thereby reducing the bonding performance and overall strength of the material.
[0097] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a high-strength and high-stability polyester cord, characterized in that: The steps include: Step S1: subjecting high-viscosity polyester chips to screw melt spinning, air blowing cooling and forming, initial application of spinning oil, heat drawing, heat setting, relaxation heat treatment, impregnation with an activator, and winding to obtain preactivated polyester fibers, and subjecting the preactivated polyester fibers to heat treatment and storage to obtain modified polyester fibers; The spinning oil is a mixed solution containing 3-aminopropyltriethoxysilane, the concentration of the oil is 15-20wt%, and the 3-aminopropyltriethoxysilane accounts for 5-20wt% in the spinning oil; The process conditions of the heat drawing are: the temperature of the hot roller is 90-150°C, and the speed of the hot drawing roller is 3000m / min-4000m / min; the process conditions of the heat setting and relaxation heat treatment are: the temperature of the hot roller is 200-255°C, and the speed of the hot roller is 4500m / min-6000m / min; The activator is a mixed solution containing caffeic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and water; The heat treatment storage specifically comprises: heat treating the preactivated polyester fiber at a temperature of 50-100° C. for a treatment time of 96-110 hours; Step S2: the modified polyester fiber is paralleled, twisted, and heat-set to obtain a polyester strand; the polyester strand is twisted into shape by a twisting machine to obtain a twisted cord; Step S3: immersing the twisted cord into a first adhesive solution for a primary immersion treatment, irradiating it with ultraviolet light, and then immersing it into a second adhesive solution for a secondary immersion treatment, and obtaining a polyester cord after drying and heat treatment.
2. The method for preparing a high-strength and high-stability polyester cord according to claim 1, characterized in that: In the step S1, the mixed solution of 3-aminopropyltriethoxysilane is composed of deionized water and 3-aminopropyltriethoxysilane in a mass ratio of (2-3): (0.2-0.4).
3. The method for preparing a high-strength and high-stability polyester cord according to claim 1, characterized in that: In the step S1, the mass ratio of caffeic acid to 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 1:(0.1-0.2).
4. The method for preparing a high-strength and high-stability polyester cord according to claim 1, characterized in that: In step S3, the preparation method of the first adhesive solution is as follows: The mercapto compound, 2-mercaptobenzothiazole, ammonia water and deionized water are mixed evenly, and then a photoinitiator and styrene-butadiene latex are added and mixed evenly to obtain a first adhesive solution.
5. The method for preparing a high-strength and high-stability polyester cord according to claim 4, characterized in that: The first adhesive solution comprises the following components by weight: 5-10 parts of mercapto compound, 1-3 parts of photoinitiator, 3-5 parts of 2-mercaptobenzothiazole, 2-4 parts of styrene-butadiene latex, 10-40 parts of ammonia water, and 30-50 parts of deionized water.
6. The method for preparing a high-strength and high-stability polyester cord according to claim 5, characterized in that: The preparation method of the thiol compound is as follows: Glutathione, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide, N,N-diisopropylethylamine and 4-pyrrolidinylpyridine are mixed evenly, deionized water and anhydrous ethanol are added, and the mixture is stirred at 20-30° C. for 30-50 minutes. Polylysine is added, and the mixture is stirred for 20-24 hours. The mixture is filtered, rotary evaporated and dried to obtain a thiol compound.
7. The method for preparing a high-strength and high-stability polyester cord according to claim 6, characterized in that: The volume ratio of the deionized water to anhydrous ethanol is 1:2, the ratio of glutathione to deionized water is 5 g / 100 mL, and the mass of polylysine is 1.5-2.0 times the mass of glutathione.
8. The method for preparing a high-strength and high-stability polyester cord according to claim 1, characterized in that: In step S3, the second adhesive solution is prepared as follows: trimethylolpropane triglycidyl ether and deionized water are mixed evenly, triethylenetetramine is added, and stirred at 60-80°C for 30-50 minutes, and then styrene-butadiene latex solution is added, and stirred at 20-30°C for 1-2 hours to obtain the second adhesive solution.
9. The method for preparing a high-strength and high-stability polyester cord according to claim 8, characterized in that: The second adhesive solution comprises the following components by weight: 5-10 parts of trimethylolpropane triglycidyl ether, 1-5 parts of triethylenetetramine, 100-110 parts of styrene-butadiene latex solution, and 90-180 parts of deionized water.
10. A high-strength and high-stability polyester cord prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Run flat tire
CN102574432A
Environment-friendly bonding accelerator as well as preparation method and application thereof
CN107459614A
Double coating fast curing solventless polyurethane adhesive and composite film material with wide adaptability of substrate and preparation method thereof
CN108084944A